Lady snowblood - Fujita, Toshiya, 1932-1997; Kaji, Meiko; Kurosawa, Toshio; Daimon, Masaaki; Okada, Eiji, 1920-1995; Nishimura, Ko (Art Free, 2005)
Από τα ματωμένα χείλη της ετοιμοθάνατης μητέρας της βγαίνει ο μοναδικός λόγος που της δίνει ζωή... θάνατος!